Anti-obesity and hepatoprotective effects of pyridoxal phosphate in rats with metabolic syndrome by raising anti-oxidant potential in both serum and liver tissue, while also decreasing hepatic nuclear factor expression - Sina Mahdavifard; Amir Hasani (Iranian Journal of Basic Medical Sciences)
Objective(s): Insulin resistance is the primary trigger of metabolic syndrome, carbonyl stress, and vitamin B6 deficiency, while the nuclear factor (NF-κB) pathway is a pivotal factor in its development. Hence, we investigated the impact of pyridoxal phosphate (PLP) on liver and kidney functions, carbonyl stress, and inflammatory markers in serum and liver tissue.Materials and Methods: The study involved four groups of rats, each consisting of eight rats: untreated normal rats (N), rats induced to have metabolic syndrome (MetS), and rats treated with PLP, labeled as N (PLP) and MetS (PLP), respectively. Metabolic syndrome was induced in rats by administering a concentrated sucrose solution for four months. The treated groups received daily PLP at 180 mg/l in their drinking water. Subsequently, the metabolic profile, NF-κB expression, indicators of gly-oxidation, inflammation, and organ function markers were evaluated. Results: PLP significantly reduced gly-oxidation, carbonyl stress, and inflammatory indicators (in both serum and liver tissue) as well as NF-κB expression, glycation, carbonyl stress, liver fat levels, glycemia, insulin resistance, and body weight (P<0.001). The treatment also prevented acute hepatitis. Conclusion: PLP had beneficial effects in the metabolic syndrome rat model, showing anti-obesity and hepato-renal protective effects. It improved metabolism and organ (liver and kidney) functions by modulating NF-κB expression, glutathione metabolism, carbonyl stress, and oxidative stress.